Radio Free Dixie : Robert F. Williams and the Roots of Black Power - Tyson, Timothy B. (Book collections on Project MUSE., 1999)
"The story of Robert F. Williams shows that independent black politics, black cultural pride, and "armed self-reliance" operated in tension and in tandem with legal efforts and nonviolent protests. Radio Free Dixie reveals that both the civil rights movement and the Black Power movement, often portrayed in clashing terms, grew out of the same soil, confronted the same predicaments, and reflected the same quest for African American freedom."